ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI PRODUK SEPATU MENGGUNAKAN METODE FULL COSTING DI UKM SEJAHTERA - Rizky Arya S; Frans Destri Bintang S, Ifnu Nur Hidayat, Paduloh (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2024)
This study aims to analyze the calculation of the cost of production of shoe products using the full costing method at UKM Sejahtera. SMEs (Small and Medium Enterprises) play an important role in a country's economy, and a good understanding of production costs is the key to their business success. The full costing method is an approach that incorporates all production costs, both variable and fixed costs, in8to the calculation of the cost of goods. In this study, production cost data from UKM Sejahtera was taken and analyzed using the full costing method. The results of the analysis show that the application of the full costing method has a significant impact on the calculation of the cost of production of shoe products in UKM Sejahtera. In this method, fixed costs are also accumulated, so that the cost of goods manufactured becomes more transparent and reflects the actual costs associated with shoe production